Content of the magazine "Ukrainskyi visnyk" of the first period of its edition as a reflection of ideological evolution of oppositional movement of the Ukrainian intelligence of 1970's - Tamara Baklashova (Cхід, 2013)
In article considered content of the magazine "Ukrainskyi visnyk" of the first period of its edition as a reflection of ideological evolution of oppositional movement of the Ukrainian intelligence in the end of the 50th - the beginning of the 80th.In the main it is reflected the history of magazine's creation and the task which were solved in a context of oppositional activity of the Ukrainian intelligence of the main period. It is mentioned, that exactly in the early seventies this movement gets new sense in connection with disappointment of youth in the possibility of developing the culture and identity in the conditions of the Soviet reality. It also gave magazine's ideological evolution for that time.